Step 1: We are given:
\[
I = \int e^{\tan \theta} (\sec \theta - \sin \theta) d\theta
\]
Distribute the terms inside the integral:
\[ \text{Let } I = \int e^{\tan \theta} (\sec \theta - \sin \theta) \, d\theta \]
\[ \text{Put } \tan \theta = t \Rightarrow \sec^2 \theta \, d\theta = dt \Rightarrow d\theta = \frac{dt}{1+t^2} \]
\[\Rightarrow I = \int e^t \left(\sqrt{1+t^2} - \frac{t}{\sqrt{1+t^2}}\right) \frac{dt}{1+t^2} \]
\[= \int e^t \left(\frac{1}{\sqrt{1+t^2}} - \frac{t}{(1+t^2)^{3/2}}\right) \, dt\]
Integrating the first part by parts, we have
\[= \frac{1}{\sqrt{1+t^2}} e^t - \int \frac{t}{(1+t^2)^{3/2}} e^t \, dt + \int \frac{t}{(1+t^2)^{3/2}} e^t \, dt + c\]
\[= \frac{e^t}{\sqrt{1+t^2}} + c\]
\[= e^{\tan \theta} \cos \theta + c\]
Thus, the final answer is \( e^{\tan \theta} \cos \theta + c \).